Determination of total phenolic contents and antioxidant capacity in Malaysian unifloral honeys / Syaliza Omar, Maisarah Abdul Hamid and Norhilmiah Hayati Mohd Yaacob - Omar, Syaliza; Abdul Hamid, Maisarah; Mohd Yaacob, Norhilmiah Hayati (Institute of Research, Development and Commercialization , Universiti Teknologi MARA, 2009)
The main objectives of this project are to determine total phenolic content, antioxidant content in honey and to identify correlation between total phenolic content and antioxidant activity. This study has been performed by using reagent; Folin-Ciocalteu reagent for determining total phenolic content and DPPH reagent for determining antioxidant content of honey. All honey samples were dissolved in distilled water to produce desired concentration. The dissolved honeys were subjected for Folin-Ciocalteu method and DPPH method. Spectrophotometer was used to determine the desired compound at 760 nm for total phenolic content and 5 17 nm for antioxidant content. The graph of total phenolic content against antioxidant activity was plotted to identify correlation between total phenolic content and antioxidant content. The results showed that the duran honey had the highest total phenolic contents, while gelan1 honey represented the highest antioxidant capacity of all honeys tested. Total phenolic contents and antioxidant capacity have been found to be dose-dependant.